Wednesday

October 22, 2014

October 22, 2014

Posted by **Sarah** on Wednesday, May 9, 2007 at 12:36pm.

express your question as

ln[(y-1)(y+1)] = -x+c

change that to exponential form

e^(-x+c) = (y-1)(y+1)

e^(-x+c) = y^2 - 1

y^2 = e^(-x+c) + 1

y = ± sqrt(e^(-x+c) + 1)

**Answer this Question**

**Related Questions**

Pre-Calc - Can you show me how to find the rectangular equation of r=2costheta...

pre calc - Express the function f(x)=1/(x-2)in the form g of h if h(x)=x-2. Find...

Pre-Calc - Can someone show me how to do this please. I am stuck. find a number ...

pre calc - Find the critical number of the function. g(t) = | 6t - 9 | t =

Pre-Calc - I am stuck solving this problem, any help please..Many thanks find ...

Pre-Calc - Please help me with this problem-I'm stuck (x-2)/(x+2) = (x+10)/x I'm...

pre calc - given x=t^2 and y=t-2 find a relationship between x amd y( express y ...

Pre Calc - Can someone help me understand how to do this: I need to find two ...

pre calc - I have a few problems from my homework that I am having trouble with...

pre calc need help - Find the indicated function value. Do not use a calculator...